'It's every breath we take here': Political astuteness and ethics in civil service leadership development. Issue 8 (16th November 2020) - Hartley, Jean; Manzie, Stella
ABSTRACT: This paper uses survey and interview research with senior civil servants to argue that leadership with political astuteness is a specific contextual requirement for public servants who work closely with politicians. Also important are technical skills, judgement and a sharp sense of ethics and integrity. The fine balance of political astuteness and other capabilities is shown in a framework about leading in an ethical way. Implications for the development of civil servants are considered.